2008
DOI: 10.1007/s12031-008-9055-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased GABAB Receptor Subtype Expression in the Nucleus of the Solitary Tract of the Spontaneously Hypertensive Rat

Abstract: Expression of GABA(B) receptor messenger RNA (mRNA) in the central nervous system was compared between the spontaneously hypertensive (SHR) and normotensive Wistar Kyoto (WKY) rat. Polymerase chain reaction (PCR) revealed all the isoforms except B1e in cortex, hypothalamus, and medulla oblongata. In the nucleus of the solitary tract (NTS) and ventrolateral medulla (VLM), the B1a-c and 1 g isoforms were present as well as B2. Real-time PCR detected significantly higher levels of B1a (p < 0.01) and B2 (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
0
13
1
Order By: Relevance
“…Studies by Sato et al (2001) have shown that lesions of the cNTS also produce a significant fall in the arterial pressure level in adult SHR, but not in normotensive rats, suggesting that the development of hypertension in this model may involve neuroplasticity within the NTS. In agreement with this hypothesis, there are several studies demonstrating relevant changes in the mechanisms of neurotransmission and neuromodulation in the NTS of SHR rats, including glutamate (Aicher et al, 2003), angiontesin II (Shan et al, 2013), GABA (Mei et al, 2003; Spary et al, 2008), nitric oxide (Hirooka et al, 2003) and inflammatory molecules (Waki et al, 2008). Altogether, these findings indicate that neurogenic hypertension is causally associated with potentiation of peripheral chemoreflex, in which plastic changes of cNTS neurons receiving the afferent inputs from the carotid bodies importantly contribute to elevate baseline sympathetic activity and strength respiratory-sympathetic coupling.…”
Section: Nts Neuroplasticity and The Development Of Cardiorespiratorymentioning
confidence: 70%
“…Studies by Sato et al (2001) have shown that lesions of the cNTS also produce a significant fall in the arterial pressure level in adult SHR, but not in normotensive rats, suggesting that the development of hypertension in this model may involve neuroplasticity within the NTS. In agreement with this hypothesis, there are several studies demonstrating relevant changes in the mechanisms of neurotransmission and neuromodulation in the NTS of SHR rats, including glutamate (Aicher et al, 2003), angiontesin II (Shan et al, 2013), GABA (Mei et al, 2003; Spary et al, 2008), nitric oxide (Hirooka et al, 2003) and inflammatory molecules (Waki et al, 2008). Altogether, these findings indicate that neurogenic hypertension is causally associated with potentiation of peripheral chemoreflex, in which plastic changes of cNTS neurons receiving the afferent inputs from the carotid bodies importantly contribute to elevate baseline sympathetic activity and strength respiratory-sympathetic coupling.…”
Section: Nts Neuroplasticity and The Development Of Cardiorespiratorymentioning
confidence: 70%
“…Increased ERa and b mRNA expression has also been observed in rat dorsal root ganglion cells in proestrus compared to metoestrus (Taleghany et al, 1999). Our ongoing studies suggest that there are region specific changes in the mRNA expression for ERa, ERb and GPR30 over the rat oestrus cycle in several CNS areas concerned with cardiovascular control (Spary et al, 2006(Spary et al, , 2007.…”
Section: Changes In Er Expression Associated With Oestrogen Levelsmentioning
confidence: 71%
“…Oestrogen receptor isoform mRNA expression in the hypothalamus and brainstem. Reverse transcription PCR was performed with isoform specific primers (Table 2) using tissue taken from the hypothalamus and medulla oblongata as previously described (Saha et al, 2004;Spary et al, 2008). Products were separated on 2% agarose gels stained with ethidium bromide.…”
Section: Changes In Er Expression Associated With Oestrogen Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated from micropunches of IML and spinal cord slices of rats (10 -15 d), anesthetized and prepared as described above. The RNA was reverse transcribed as previously described (Spary et al, 2008). PCR was performed with 0.4 M primers (␣5 forward 5Ј, TGACCAAAACCCTCCTTGTCTTCT-3Ј, ␣5 reverse 5Ј, AC-CGCAGCCTTTCATCTTTCC-3Ј; ␦ forward 5Ј, GCCAAGTCTGC-CTGGTTCCA-3Ј, ␦ reverse 5Ј, GGAGACCCAGGACATGGCAA-3Ј) (Spary et al, 2008).…”
Section: Introductionmentioning
confidence: 99%